Intelectuales e izquierda peronista. El surgimiento de una cultura política en la Argentina de la proscripción al peronismo (1955-1973) - Valeria A. Caruso (Nuevo mundo - Mundos Nuevos, 2021)
This doctoral research studies the formative process of the Peronist left as a political culture during the period of the proscription of Peronism (1955-1973). This work argues that in the course of those eighteen years, different Peronist referents deployed ideas, initiatives and actions that made it possible to reconsider the proscribed political force as an anti-capitalist doctrine of national liberation.In the first part of the writing, the starting points that guided this approach to intellectual history are exposed, which made possible a differential approach to the classic history of ideas, as it allowed to address the ideological projections expressed by the referents of the Peronist left in relationship with the contexts they tried to create through the practices they carried out.In the second part, the arrival points of this inquiry are presented based on the analysis of the political and intellectual trajectories of John William Cooke, Alicia Eguren, Juan José Hernández Arregui, Rodolfo Ortega Peña, Eduardo Luis Duhalde, and Raimundo Ongaro. The weeklies 18 de Marzo, Compañero and the discussions that took place around the meanings that the notion of "national socialism" contained for the Peronists at the beginning of the '70s are also examined.